PERUBAHAN NORMA ETIKA DALAM HUBUNGAN SOSIAL DI PLATFORM MEDIA SOSIAL - Atiqah Revalina; Aslan Aslan (Jurnal Komunikasi, 2025)
Changes in ethical norms in social relationships on social media platforms are an inevitable phenomenon in the digital age. Social media has changed the patterns of communication and interaction within society, providing ease in sharing information but also presenting new challenges related to ethics, such as the spread of hoaxes, cyberbullying, privacy violations, and shifts in values of politeness. This transformation has led to a decline in empathy, an increase in self-validation culture, and the emergence of new moral dilemmas that have never been faced before. Therefore, digital literacy, ethical awareness, and collaboration among various parties are needed to ensure that social relationships on social media remain healthy, harmonious, and civilised